The Impact of Equity-preferences on the Stability of Heterogeneous International Agreements - Andreas Lange (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This paper studies the impact of equity considerations on the stability of international agreements between heterogeneous countries. We show that allowing countries to finance abatement projects in developing countries which, due to equity-reasons, have no binding emission targets can reduce the number of cooperating countries and thereby be welfare-decreasing. Equity-concerns in industrialized countries regarding the gap between per-capita emission levels of industrialized and developing countries lead to an increased reduction in industrialized countries but do not qualitatively change the incentives to cooperate. Only if countries are inequality-averse with respect to potential differences between their abatement targets and those of other industrialized countries is the inclusion of developing countries generally profitable both in terms of participation rates and of emission reduction.
Keywords: Q0; H41; C7; D63; 330; international environmental negotiations; equity preference; coalition formation; per capita emission levels; inequality aversion; Umweltabkommen; Klimaschutz; Verhandlungen; Gerechtigkeit; Präferenztheorie; Koalition; Nord-Süd-Beziehungen; Theorie